Hubungan Penggunaan Alat Kontrasepsi Hormonal Dengan Kenaikan Berat Badan - Etni Dwi Astuti; Evita Aurilia Nardina (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
The development of the National Family Planning Movement is aimed at improving the quality of human resources. The family, as the smallest group of human resources, has both emotional and physical bonds. Injectable contraception in Indonesia is one of the most popular contraceptive methods. Users of the DMPA (Depo Medroxyprogesterone Acetate) contraceptive, also known as the 3-month injectable contraceptive, on average experience a weight gain of 11 pounds or 5.5 kilograms and an increase in body fat by 3.4% over two to three years of use. Meanwhile, with monthly injectable contraception, the side effects on weight gain are very mild, resulting in only a slight increase in body weight002. Research objective to determine whether there is a relationship between the use of hormonal contraceptive methods, especially the DMPA injectable, and weight gain. The research method used is a quantitative correlation analysis with an observational study and a cross-sectional approach. The population consists of mothers using the DMPA injectable, with 47 respondents. The sampling technique used is non-probability sampling with a purposive method. The test used is the chi-square test. Research Results, there is a relationship between the use of DMPA injectable contraception and weight gain (Chi-square: 7.362 and p-value: 0.025).